Literature review on fish parasites of Al-Furat fish farm, Babylon province, Iraq - Mhaisen, Furhan T.; Al-Niaeem, Khalidah S.; Al-Zubaidy, Ali B. (Iraqi Journal of Aquaculture, 2022)
The paper reviews all the reports concerning the parasitic fauna of the three species of carps cultured in Al-Furat fish farm, Babylon province, mid Iraq. These fishes included the common carp (Cyprinus carpio), the grass carp (Ctenopharyngodon idella) and the silver carp (Hypophthalmichthys molitrix) as well as the mullet (Liza abu) found in the same farm. The parasitic fauna included 60 valid parasite species: ten protozoans, three myxozoans, 29 monogeneans, one trematode, five cestodes, three nematodes, two acanthocephalans, six crustaceans and one mollusc. The common carp was found to harbour 56 species of parasites, the grass carp 25 species, the silver carp 25 species and the mullet six species. The parasitic species were revised and some were synonymised in accordance with latest internet taxonomical accounts. A host- parasite list was prepared for each host species which included all documented literature concerned with this farm.